Réponses

2014-05-10T23:19:17+02:00
 2: non
1: non
0: non
-1:non
-2: oui
-3:non

la solution de l'équation est -2
3x +17=7-2x
= 3x +17 -17 +2x= 7-2x -17 +2x
= 5x=-10
= 5x/5= -10/5
x= -2
2014-05-10T23:23:52+02:00
Pour x = 2 
3*2 + 17 = 6 + 17 = 23 et 7 - 2*2 = 7 - 4= 3 donc 3*2 + 17 ≠ 7 - 2*2 donc 2 n'est pas solution

Pour x = 1
3*1 + 17 = 3 + 17 = 20 et 7 - 2*1 = 7 - 2 = 5 donc  3*1 + 17 ≠ 7 - 2*1 donc 1 n'est pas solution 

Pour x = 0 
3*0 +17 = 17 et 7 - 2*0 = 7 donc 3*0 + 17 ≠ 7-2*0 donc 0 n'est pas solution 

Pour x = -1 
3*(-1) + 17 = -3 + 17 = 14 et 7 - 2*(-1) = 7 + 2 = 9  donc 3*(-1) + 17 ≠ 7 - 2*(-1) donc -1 n'est pas solution 

Pour x =  -2
3*(-2) + 17 = -6 + 17 = 11 et 7 - 2*(-2) = 7 + 4 = 11 donc 3*(-2) + 17 = 7 - 2*(-2) donc -2 est solution

Pour x = -3 
3*(-3) + 17 = -9 +17 = 8 et 7 - 2*(-3) = 7+6 = 13 donc 3*(-3) + 17 ≠ 7 - 2*(-3) donc -3 n'est pas solution